Knowledge sharing - Hejase, Hussin J. (2014)
For many companies today, the environments in which they operate have changed dramatically over the last decades. The atmosphere of corporate environment relies heavily on aspects concerning its workers and in particular its knowledge workers. Companies worldwide, in order to stay competitive, have started shifting their approach and outlook on how business should be conducted and as to what knowledge aspects are important. Knowledge sharing behavior varies within and between organizations. There are a number of factors that either motivate or hinder such a behavior. However; how these factors influence employees' motivation for knowledge sharing has not been carefully tested within Lebanese organizations. Objectives: Given the increasing importance of knowledge capital and deployment of information technology to facilitate knowledge transfer in organizations, this paper aims: 1) To examine knowledge sharing attitudes within Lebanese organizations so as to study the factors that influence motivation for knowledge sharing; 2) To analyze how organizational and human factors influence the knowledge sharing behavior within these organizations. Method: Mixed method approach. A qualitative approach was adopted to review current secondary data and information to prepare a background for the research in question. A quantitative approach using a questionnaire survey was used to collect data from a sample of 148 Lebanese employees in order to assess and validate the research model in question. Results: A relationship has been proved to exist between knowledge sharing and trust, management’s support, culture and psychological ownership of knowledge, indicating the importance of such factors as prerequisites of the success of knowledge sharing. Conclusions: The results of this study have implications for staff and managers in organizations. Organizations have to create a culture that is pro-knowledge sharing, where knowledge sharing is valued by everyone, and strategies that are more knowledge friendly are implemented; this is done through the mentoring programs, creating communities, conferences and through generating a vision that emphasizes knowledge and its importance.